Kemandirian Belajar Matematika Siswa Melalui Model Problem Based Learning (PBL) di Kelas VII SMP Negeri 3 Pulau Punjung - Novita, Dini; Medika, Gema Hista (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study was to find out whether the Problem Based Learning (PBL) approach increases student independence in learning mathematics. This type of research is pre-experimental or Static Group Comparison methodology. The study population is all grade VII students enrolled in SMP Negeri 3 Pulau Punjung, Dharmasraya Regency for the 2022–2023 school year. The technique used is random sampling. The research sample came from grade VII.1 students who were used as an experimental class with a total of 22 students, and VII.4 which was used as a control class with a total of 20 students. The results of the questionnaire analysis of students' independence in mathematics learning were obtained tcalculate = 5.042 and ttabel = 1.68. because if tcount>ttable then H0 is rejected. Therefore, it can be concluded that there are differences in student learning independence in the problem-base learning model compared to conventional learning.